Pig Butchering in Cybersecurity: A Modern Social Engineering Threat - Dr. Sharon L. Burton; Dr. Pamela D. (Vickerson) Moore (SocioEconomic Challenges)
Pig butchering is an escalating cybersecurity threat that exploits social engineering to build trust and execute financial fraud. The relevance of this research problem lies in the growing incidence and sophistication of these scams, which have severe financial and psychological impacts on victims. The main purpose of this research is to uncover the methods used in pig butchering scams and their impact on individuals and businesses. The research focuses on digital platforms such as social media, dating apps, and professional networking sites, chosen for their wide user bases and the ease of establishing personal connections. The study period encompasses recent developments from the past five years to capture the evolving nature of these scams. The research utilizes a qualitative literature review as its primary method, drawing on academic articles, industry reports, and case studies. The study's statistical basis includes data from law enforcement agencies, cybersecurity firms, and victim reports. Key findings confirm the effectiveness of proactive cybersecurity measures, such as continuous education and specialized services, in mitigating pig butchering scams. The research hypothesis, stating that these measures can significantly reduce scam success rates, is supported by the data. Results indicate that enhancing cybersecurity protocols and training programs is crucial for protecting against such threats. Future research should focus on developing predictive models and integrating AI and machine learning for better detection and prevention. This study provides valuable insights for policymakers, cybersecurity professionals, and educators, highlighting the need for international cooperation and advanced technological defenses to combat this pervasive threat.